A methodology used for the development of an Air Traffic Management functional system architecture - Costa,Teixeira Santos PL; Antunes,Monteiro PA; Studic,M; Majumdar,A (Reliability Engineering and System Safety, 2017)
The Air Traffic Management (ATM) system provides a safe, economical, efficient, dynamic and integrated management of air traffic and airspace through the collaborative integration of humans, infrastructure (technology and facilities) and organisations. At present, it is widely accepted that the ATM system is one of the leading complex socio-technical systems in terms safety performance. To maintain this reputation, safety management of the ATM system needs to be able to cope with not only rising travel demand, but also the increased automation, the tighter coupling between its component elements and greater complexity of the ATM system itself. As a way of ensuring this, in Europe the European Union Regulation 1035/2011 requires the Air Navigation Service Providers (ANSPs) responsible for the provision of ATM, to describe and model their systems by accounting for the functional interactions between the equipment, procedures and human resources of the ATM system. However, despite the number of available models of the ATM system, none of them meets this requirement. Typically the existing models focus on the technical functions and describe the system usage via operational scenarios. Therefore this paper proposes a novel methodology used for the development of a functional system architecture − Model of ATM Reality In Action (MARIA) − with the aim to provide a sound base for system analysis, including safety, namely by describing the whole system and the interdependencies between its functions. By overcoming the limitations of the existing models MARIA has the potential to improve understanding of the ATM services safety, system resilience and meet the requirements of the Regulation 1035/2011. Lastly, the methodology applied in the ATM domain presented in this paper is equally transferable to systemic modelling of other complex socio-technical systems.